1999
DOI: 10.1103/physrevlett.83.364
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure of the Heavy Fermion MetalLiV2O4

Abstract: The electronic structure of the first reported heavy fermion compound without f electrons, LiV 2 O 4 , was studied by an ab initio calculation method. As a result of the trigonal splitting and d-d Coulomb interaction, one electron of the d 1.5 configuration of the V ion is localized and the rest partially fills a relatively broad conduction band. The effective Anderson impurity model was solved by the noncrossing-approximation method, leading to an estimation for the single-site Kondo energy scale T K . Then, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
130
3

Year Published

2002
2002
2004
2004

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 124 publications
(139 citation statements)
references
References 19 publications
6
130
3
Order By: Relevance
“…The orbital occupation, which confirms the earlier conjecture based on the LDA+U approach, 33 can be readily understood from the previous analysis of the LDA band structure. There we found that the center of mass of the a 1g orbital is 0.26 eV lower than the corresponding value for the e π g orbitals.…”
Section: B Single-particle Propertiessupporting
confidence: 75%
See 4 more Smart Citations
“…The orbital occupation, which confirms the earlier conjecture based on the LDA+U approach, 33 can be readily understood from the previous analysis of the LDA band structure. There we found that the center of mass of the a 1g orbital is 0.26 eV lower than the corresponding value for the e π g orbitals.…”
Section: B Single-particle Propertiessupporting
confidence: 75%
“…The value and the sign of the trigonal splitting will determine the orbital in which the V 3d electrons should be localized when a strong Coulomb interaction, which is larger than the bandwidth, is taken into account. 33 We found that this trigonal splitting value is very sensitive to the accuracy of the band structure calculations. In order to increase the accuracy, the overlap between atomic spheres in our LMTO calculation was set to zero and more empty spheres were introduced.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations